Pembangunan Pertanian Pedesaan Di Lombok Utara: Institusi, Tata Kelola, Dan Pemberdayaan Petani - Siti Zainab; Hayati Hayati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
Agricultural development in dryland and archipelagic regions faces structural constraints such as limited natural resources, weak infrastructure, and restricted market access. These conditions require adaptive policy approaches that are institution-based and oriented toward farmer empowerment. North Lombok Regency represents a typical dryland agroecological area where agriculture remains the primary livelihood for rural communities. This study aims to review recent literature on the dynamics of rural agricultural development in North Lombok, with a focus on farmer empowerment, farming systems, and the role of local institutions and governance. A critical narrative literature review was conducted on scientific articles and policy reports published between 2020 and 2025. The findings indicate that agricultural development programs in the region are still predominantly project-based, including training activities, demonstration plots, and technical assistance. These interventions have improved farmer capacity in the short term but have not been fully institutionalized within a sustainable regional development governance system. Therefore, strengthening local institutions and transforming development approaches toward a more systemic, participatory, and sustainable agricultural model is essential.